Humanitarian Mission in Pediatric Cardiothoracic Surgery: A Recipient's Perspective - Mohd Zain, Mohd Rizal; Shamsuddin, Ahmad Mahir; Mamat, Ahmad Zuhdi; Mokhtar, Ariffin Marzuki; Ali, Saedah; Chen, Yen Chuan; Corno, Antonio F. (Frontiers in Pediatrics, 2019)
Introduction: Pediatric cardiac surgical mission programs are deemed as common practice, especially in developing nations funded by international non-governmental organizations (NGOs). This article presents and discusses the results and strategies implemented by this partnership, aiming at achieving the autonomy of the local center by this collaboration. Materials and Methods: A retrospective review was conducted on patients with congenital heart disease who underwent surgical intervention from the beginning of the NGO collaboration (September 2015) until November 2018 in an existing cardiac center. In between those visits, any congenital heart disease patient with Risk Adjustment Congenital Heart Surgery (RACHS)-1 Category 1–3 would be discussed in a local multi-disciplinary meeting with regards to the feasibility of the surgery being performed by the local members. Results: A total of 60 operations were performed during the trips. Throughout the visit, 46% (28) of the operations were performed by the local surgeon, with or without assistance from the visiting surgeon. Between September 2015 and November 2018, 27 cases were also performed by the local team independently. For the 27 cases performed by the local team independently, the median age of the patient was 42 days (ranging from 14 days to 20 years old), with median body weight of 3.2 kg (ranging from 2.8 to 64 kg). Conclusion: Humanitarian pediatric cardiac surgical missions are safe to be done for the population in need. In order to achieve autonomy, continuous efforts by both teams are crucial, as the cooperation by the two parties ensures that the objectives are achieved.